What kinds of Chinese "Geese" are flying to Africa? Evidence from Chinese manufacturing firms - Deborah Brautigam; Tang Xiaoyang; Ying Xia (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2018)
In a thoroughly researched piece, Brautigam, Tang, and Xia offer a preliminary analysis of the nature of Chinese manufacturing investments in Africa, focusing predominantly on four countries – Ethiopia, Ghana, Nigeria, and Tanzania. Drawing on fieldwork conducted between 2014 and 2016, they explore the varieties of existing Chinese manufacturing investment and the sectors into which Chinese companies are investing. Several investors fit the model of Akamatsu's "flying geese" (large firms seeking new locations for production as part of global networks and value chains), yet the authors also identified three other kinds of "geese": large, strategic, local market-seeking geese; raw material-seeking geese; and small geese traveling together in flocks. The different kinds of firms offer different kinds of development opportunities and challenges for structural transformation in Africa.
Keywords: 330